Optimizing reactive power reserves by using Artificial Immune System technique / Lily Suryani Suaidi - Suaidi, Lily Suryani (2006)
Voltage collapse phenomenon in a power system has been attributed to a lack of sufficient reactive power reserves when the power system experiences a heavy load or severe contingencies. The voltage instability is characterized in such a way that voltage magnitudes of the power system buses decrease gradually and rapidly in the voltage magnitude at collapse point.